Therapeutic approach to patients with chronic orofacial pain with temporomandibular disturbed - Moura, Adolpho Marlon Antoniol; Matos, Bruna Marquezini; Sousa, Saulo Machado Moreira de; Pompei Filho , Horácio (Brazilian Journal of Case Reports, 2022)
Temporomandibular disorder (TMD) is a term that encompasses a series of dysfunctions and disorders that affect the temporomandibular joint (TMJ), masticatory muscles and associated structures. These disorders are characterized by a set of signs and symptoms that may include joint noises, such as clicking and crackling, tooth wear, limited mandibular movement, accompanied or not by facial, cranial and periauricular pain. Here, we reported the clinical conduct of a patient with muscle TMD. Patient with chronic pain complaint in the cervico-craniofacial region, signs of bruxism, mouth opening limitation and masseteric hypertonia. The diagnosis was TMD of bilateral masseteric muscle origin, without trigger points. Heat thermotherapy was prescribed, myofacial and myofunctional physiotherapy, rigid Michigan stabilizer plate making, postural correction, and cognitive-behavioral therapy. The patient presented a gradual evolution of the clinical condition and after 90 days reported remission of approximately 95% of the symptomatological complaints, such as an improvement in the quality of sleep at night, without medication assistance, reduction in pain crises, and full mouth opening (44mm). It is concluded that the correct diagnosis and full patient adherence to the treatment proposed in this study provided relief in painful symptoms and biopsychosocial aspects.